Constitutive memory equations for auxetic materials - Caputo, Michele; Ruggiero, Vittorio (Mathematical Modelling and Analysis, 2025)
In this note we suggest a set of constitutive equations for anelastic materials whose internal structure can present anomalous variations resulting from external effects of tension/compression, as in auxetic media. For these problems we require of a new function related with the variation of internal structure, which allows us to define a threshold separating the internal structure media from the classic ones. The equations are formulated in the case of static problems but also when the material has memory or plastic properties in addition to auxetic ones. In order to limit the complexity of the formulae, the discussion is limited to the case where the perturbation is one dimensional, which however does not limit the significance of the results.